2011
DOI: 10.1248/bpb.34.1240
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Pharmacokinetic Studies of Silodosin, a New .ALPHA.1A-Adrenoceptor Selective Antagonist, in Healthy Chinese Male Subjects

Abstract: Benign prostatic hyperplasia (BPH) is a common clinical disorder in elderly males. It causes a variety of urological symptoms, including a poor stream of urine flow, dribbling and nocturia. Adrenergic a-receptors are the molecular target for the clinical treatment of arterial hypertension and benign prostatic hyperplasia. Adrenergic a 1 -receptor (a 1 -AR) blockers are widely used as first-line drugs in treating lower urinary tract symptoms resulting from BPH 1,2) because they are able to improve rapidly subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Safety studies of silodosin, a new α1A-adrenoceptor selective antagonist, in healthy Chinese male subjects showed that mild adverse events, including dizziness, postural hypotension, and headache, were observed. [56] Pantoprazole (40 mg once daily) appears to be well tolerated during short term oral administration, with diarrhea (1.5%), headache (1.3%), dizziness (0.7%), pruritus (0.5%), and skin rash (0.4%) representing the most frequent adverse events. [57] Acute aripiprazole poisonings most commonly result in vertigo or dizziness, sedation, sinus tachycardia, nausea / vomiting, or dystonic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Safety studies of silodosin, a new α1A-adrenoceptor selective antagonist, in healthy Chinese male subjects showed that mild adverse events, including dizziness, postural hypotension, and headache, were observed. [56] Pantoprazole (40 mg once daily) appears to be well tolerated during short term oral administration, with diarrhea (1.5%), headache (1.3%), dizziness (0.7%), pruritus (0.5%), and skin rash (0.4%) representing the most frequent adverse events. [57] Acute aripiprazole poisonings most commonly result in vertigo or dizziness, sedation, sinus tachycardia, nausea / vomiting, or dystonic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The literature reveals very few methods for the determination of SLD in biological samples or pharmaceutical formulations (Nair, Kumar, Sharma, & Karia, ; Shaik, Saladi, & Sait, ; Vishnuvardhan et al, ; Wang, Xiang, Cui, Zhao, & Zhou, ; Zhao et al, ; Zhou et al, ). A liquid chromatography–tandem mass spectrometry (LC–MS/MS) method has been reported for the estimation of SLD in human plasma with a sensitivity of 0.5 ng/mL (Zhao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Such increased selectivity for α 1A -AR is envisaged to provide additional relief from LUTS in patients with BPH without increasing the rate of serious adverse cardiovascular events [5]. In this editorial, we evaluate the capabilities and scope of the existing bioanalytical methods and propose a novel fit-for-purpose liquid chromatography-tandem mass spectroscopy (LC-MS/MS) method in human plasma that can meet the current requirements for the analysis of silodosin and its metabolites.Bioanalytical platforms for silodosin: past, present & future Since its approval in 2008, there have been very few bioanalytical methods developed for the quantitation of silodosin [6][7][8]. LC-MS/MS so far has been the preferred technique for analysis; however, a complete account of bioanalytical method development incorporating sample extraction, chromatographic separation and mass spectrometric detection is currently limited.…”
mentioning
confidence: 99%
“…Bioanalytical platforms for silodosin: past, present & future Since its approval in 2008, there have been very few bioanalytical methods developed for the quantitation of silodosin [6][7][8]. LC-MS/MS so far has been the preferred technique for analysis; however, a complete account of bioanalytical method development incorporating sample extraction, chromatographic separation and mass spectrometric detection is currently limited.…”
mentioning
confidence: 99%
See 1 more Smart Citation